Dynamic Model and PD Control with Forces Compensation of Dual-Stage Gough-Stewart Platform - Ha Huy Hung; Phan Bui Khoi; Hoang Quang Chinh; Quan Dinh Nguyen; Ha Thanh Hai (Journal of Machine Engineering)
This paper investigates a dual-stage Gough-Stewart platform. The lower platform is responsible for simulating the oscillations of moving vehicles such as cars, ships, and airplanes. The upper platform is connected to devices that require either balance stabilization or motion stabilization according to specific requirements. The dynamic model of the robot system is derived in a general form based on the Lagrange equations of motion with Lagrange multipliers. Using these equations in a compact form, a PD controller with forces compensation in task space is designed for the robot system. Oscillation generation and balance stabilization are computed and simulated using the kinematic and dynamic parameters of two Bosch Rexroth robots. The computation and simulation results demonstrate the dynamic model's accuracy and the controller's effectiveness.